2008
DOI: 10.1007/s00296-008-0643-3
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent meningitis revealing a Behçet’s disease

Abstract: The aim of the present study was to describe a case of Behçet's disease revealed by a recurrent meningitis and to review literature on these two conditions. We describe the case of a 25-year-old man who presented four episodes of recurrent meningitis without any locoregional cause and developed oral and genital ulcerations few months later. Behçet's disease is a chronic, multisystemic disorder with variable prevalence in different geographical areas. Its neurological manifestations are well recognized. Both ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…It can be categorized into three main groups: parenchymal central nervous system (CNS) involvement, which includes brainstem, cerebral, spinal cord and optic neuropathy; nonparenchymal CNS involvement which includes cerebral venous thrombosis, intracranial hypertension syndrome, and acute meningeal syndrome; and peripheral nervous system involvement [ 1 4 ]. Although isolated meningeal presentation in NBD is quite rare, several cases have been reported as acute meningitis, and recurrent meningitis [ 2 7 ]. We suggest that if NBD affects the meninges, the meningeal chronic inflammation by NBD could be progressed to HP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be categorized into three main groups: parenchymal central nervous system (CNS) involvement, which includes brainstem, cerebral, spinal cord and optic neuropathy; nonparenchymal CNS involvement which includes cerebral venous thrombosis, intracranial hypertension syndrome, and acute meningeal syndrome; and peripheral nervous system involvement [ 1 4 ]. Although isolated meningeal presentation in NBD is quite rare, several cases have been reported as acute meningitis, and recurrent meningitis [ 2 7 ]. We suggest that if NBD affects the meninges, the meningeal chronic inflammation by NBD could be progressed to HP.…”
Section: Discussionmentioning
confidence: 99%
“…Parenchymal and non-parenchymal involvements are the most frequent types of NBD, while isolated meningeal involvement is rare. Several studies have reported cases with meningeal involvement, such as meningitis [ 2 3 ]. Hypertrophic pachymeningitis (HP) is a rare chronic inflammatory meningeal disorder associated with many conditions and characterized by a diffuse or localized thickening of the dura mater.…”
Section: Introductionmentioning
confidence: 99%
“…Esta inflamación también se puede deber a tumores primarios o metastásicos, hipersensibilidad a medicamentos y enfermedades autoinmunes como la de Behçet, vasculitis y lupus eritematoso sistémico. 17,18 Lo anterior indica que si un paciente regresa a la institución con síntomas meníngeos sugestivos de MR se lo debe estudiar y tratar interdisciplinariamente para hacer el diagnóstico y, sobre todo, aplicar oportunamente un tratamiento adecuado de forma que se prevengan las secuelas.…”
Section: Etiologíaunclassified